Developing Marketplace-Based Online Store as an Adaptation to Online Purchase Trends - Fitriani, Sabrina; Valentika, Nina (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
The presence of the Covid-19 pandemic is the main cause of the online buying trend. This is because the whole world is imposing social restrictions simultaneously, thus encouraging the birth of consumption pattern adaptations, with the digital purchasing model. These conditions require business actors to develop digital business concepts or e-commerce. One of the digital sales models is to build a marketplace-based online store. This research was conducted aiming to analyze the effectiveness of the influence of marketplace-based digital shops on purchase intention mediated by trust. To answer this goal, a quantitative study was carried out using the structural equation analysis method. The number of respondents is set at 200 people from millennial workers. Research data was collected primary by distributing questionnaires. The results of the study explain that there has been a change in purchasing patterns, from direct purchases to online purchases. Then, consumers feel that online purchases provide more guarantees of trust in service, price and satisfaction. So consumers assess, there is no doubt to make buying and selling transactions online.